Semiconducting properties of Al doped ZnO thin films - Al-Ghamdi, Ahmed A.; Al-Hartomy, Omar A.; El Okr, M.; Nawar, A. M.; El-Gazzar, S.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2014)
Aluminum doped ZnO (AZO) thin films were successfully deposited via spin coating technique onto glass substrates. Structural properties of the films were analyzed by X-ray diffraction, atomic force microscopy (AFM) and energy dispersive X-ray spectroscopy. X-ray diffraction results reveal that all the films are polycrystalline with a hexagonal wurtzite structure with a preferential orientation according to the direction (002) plane. The crystallite size of ZnO and AZO films was determined from Scherrer's formula and Williamson-Hall analysis. The lattice parameters of the AZO films were found to decrease with increasing Al content. Energy dispersive spectroscopy (EDX) results indicate that Zn, Al and O elements are present in the AZO thin films. The electrical conductivity, mobility carriers and carrier concentration of the films are increased with increasing Al doping concentration. The optical band gap (E-g) of the films is increased with increasing Al concentration. The AZO thin films indicate a high transparency in the visible region with an average value of 86%. These transparent AZO films may be open a new avenue for optoelectronic and photonic devices applications in near future. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ZnO; Al-doped; Sol-gel; Thin film; Optical and electrical properties